Dejavnosti raziskovalne skupine SLOfit med epidemijo COVID-19 - Potočnik, Žan Luca (Šport (Ljubljana), 2021)
On March 11th, 2020, the World Health Organization declared a worldwide pandemic of the SARS-CoV-2 virus, followed by a declaration of epidemic in Slovenia one day later. Various restrictions were issued regarding limiting of movement and online schooling and remote working. The SLOfit research group took action immediately. They proposed an idea for the national campaign vadidoma trainathome and presented national physical activity guidelines for use during epidemics, as well various recommendations for physical education, recreational and competitive sports. Raising public awareness was an important mission. They participated in more than 25 media interviews and public statements, published four articles in peer-reviewed journals with high impact factors, more than 40 articles in the online journal SLOfit nasvet SLOfit advice, as well as more than 250 Facebook posts and participated in 18 round table discussions and expert panels. An important part of their work was the proposal of countermeasures for effects of insufficient physical activity on the physical fitness of children and adolescents and within that a development of the COVID-19 FITbarometer, a barometric tool for assessing the implementation of the countermeasures. It has been more than a year since the beginning of the pandemics and we still can't precisely predict its ending, thus we think continuing with the research is crucial to support all who are battling against the negative effects of pandemic.
Keywords: awareness raising; COVID-19; epidemic; epidemije; measures; ozaveščanje; physical activity; raziskovalno delo; research work; SLOfit; sport; šport; telesna dejavnost; ukrepi